Differential diagnosis of central lymphoma and high-grade glioma: dynamic contrast-enhanced histogram. (September 2020) - Zhang, Han-wen; Lyu, Gui-wen; He, Wen-jie; Lei, Yi; Lin, Fan; Feng, Yu-ning; Wang, Meng-zhu
Background: In clinical diagnosis, some central nervous system lymphomas (CNSL) are difficult to distinguish from high-grade gliomas (HGG). Purpose: To evaluate the diagnostic efficacy of the histogram analysis of dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) in the identification of CNSL and HGG. Material and Methods: In all, 43 patients diagnosed with HGG (n = 28) and CNSL (n = 15) by histopathology underwent DCE-MRI scanning. Differences in histogram parameters based on DCE-MRI between HGG and CNSL were analyzed by Mann–Whitney U test. In addition, receiver operating characteristic (ROC) analysis was performed. Short-term follow-up of patients was performed using Kaplan–Meier analysis to explore the survival rates of HGG and CNSL. Results: For the ROC curve analysis, we demonstrate that the 10th percentile of K trans (area under the curve [AUC] = 0.912, sensitivity = 86.7%, specificity = 92.9%), Kep (AUC = 0.940, sensitivity = 93.3%, specificity = 79.6%), Ve (AUC = 0.907, sensitivity = 86.7%, specificity = 89.3%), and AUC (AUC = 0.904, sensitivity = 86.7%, specificity = 92.9%) were significantly different between the CNSL and HGG groups ( P < 0.001), with high diagnostic efficiency. Table 2 shows that the histogram features based on AUC maps (10th, 25th, median, 75th, 90th, and mean) were always significantly higher in the CNSL group than in the HGG group ( P < 0.001). There was no significant difference in Vp or in the 75th, 90th and mean of K trans, Kep, and Ve between the CNSL and HGG groups ( P > 0.05). Conclusion: A histogram analysis of DCE-MRI identified significant differences between HGG and CNSL, and this will help in the clinical differential diagnosis of these conditions.